Психологические особенности взаимодействия в футбольных командах - Sultonv, Baxtiyor (Физическое воспитание, спорт и здоровье, 2022)
The article considers the ability to work in a team. The article highlights the psychological peculiarities of the development of the ability to work in a sports team of adolescents and youths playing football.